FCC metal-like deformation behaviour of Ir3Nb with the L12 structure - Okamoto, Norihiko L.; Takemoto, Shohei; Chen, Zhenghao M.T.; Yamaguchi, Masatake; Inui, Haruyuki (International journal of plasticity, 2017)
The deformation behaviour of Ir3Nb with stoichiometric and off-stoichiometric compositions has been investigated as functions of crystal orientation and deformation temperature. The critical resolved shear stress (CRSS) for (111)[1¯01] slip in stoichiometric Ir3Nb exhibits a marginal temperature dependence at all temperatures with neither strong negative temperature dependence at low temperatures nor positive (anomalous) temperature dependence at high temperatures. This behaviour is similar to that usually observed in many pure FCC metals such as Al and Ni and cannot be classified into any of the categories of L12 compounds previously proposed based on the temperature dependence of CRSS in relation to the dissociation scheme of the [1¯01] dislocation. The CRSS for (111)[1¯01] slip exhibits orientation dependence, neither. The [1¯01] dislocation dissociates into the anti-phase boundary (APB)-type scheme and is observed to be smoothly curved on the (111) slip plane at all temperatures, indicating the planar core structure. This is exactly what is known for the perfect dislocation in many pure FCC metals and is the reason for the observed FCC metal-like deformation behaviour of Ir3Nb. The absence of yield stress anomaly in Ir3Nb is discussed in terms of anisotropy in planar fault energies and elastic constants calculated by first principles calculations and experimentally determined in the present study. [Display omitted] •The deformation behaviour of Ir3Nb (Ir-25, 28 at.%Nb) has been investigated.•Ir3Nb exhibits a marginal temperature dependence of yield stress from 77 to 1773 K.•This behaviour is similar to that usually observed in many pure FCC metals.•Ir3Nb cannot be classified into any of the existing categories of L12 compounds.•The [1¯01] dislocation dissociates in the anti-phase boundary (APB)-type scheme.